From Confiscation to Prevention: Asset Confiscation and the Impoverishment of Corruptors in Islamic Jurisprudence - Norfazilah; Andi Marlina; Rasna; Wahidin (Faculty of Sharia and Law, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
This research is motivated by the weak deterrent effect on corruption perpetrators in Indonesia, where imprisonment, fines, and compensation have not been able to eliminate economic benefits or recover state losses. The formulation of this research problem involves two key aspects: first, how Islamic jurisprudence views the policy of impoverishing corruptors through asset confiscation; second, how the concept and mechanism of impoverishing corruptors are applied in the Indonesian positive legal system and Islamic jurisprudence. This study employs a normative juridical approach, utilizing statutory guidelines, conceptual designs, case studies, and a comparative analysis of asset forfeiture models in Malaysia, Singapore, the UAE, and Saudi Arabia. Research findings suggest that depriving corruptors of their assets is effective in stripping them of their economic benefits, recovering state losses, and enhancing the deterrent effect. From a fiqh jinayah perspective, this policy is legitimate as a form of ta'zīr punishment that is relevant to the maqāṣid al-sharī‘ah, especially in safeguarding assets (ḥifẓ al-māl) and preventing public harm. This study emphasizes the need to strengthen asset confiscation through the ratification of the Asset Confiscation Bill and the implementation of proportional and accountable non-conviction-based asset forfeiture. The novelty of this study lies in the comprehensive integration of positive law, deterrence theory, and the principles of fiqh al-jinayah to establish moral, juridical, and Sharia legitimacy for the strategy of impoverishing corruptors.